AUTHORITY OF RELIGIOUS COURT IN SETTLEMENT OF SHARIAH BANKING DISSOLUTION - Astanti, Dhian Indah; Heryanti, B.Rini; Juita, Subaidah Ratna (Tadulako University, 2018)
The principle of Islamic banking is part of Islamic teachings relating to the economy. One of the principles in Islamic economics is the prohibition of usury in its various forms, and using the system, among others, in the form of profit sharing principles. With the principle of profit sharing, Islamic banks can create a healthy and fair investment climate because all parties can share both the benefits and potential risks that arise so that they will create a balanced position between the bank and its customers. Seeing the development of Islamic banks so far, sharia principles which are the main foundation of Islamic banks in carrying out their duties have not been able to be implemented and enforced optimally, especially in the event of a dispute between parties, Islamic banks and their customers. This study aims to determine and understand the authority of the Religious Courts in resolving sharia banking disputes and the principles of handling sharia banking dispute resolution. This research is a sociological juridical legal research. This approach was chosen considering that in order to achieve the objectives of the study not only based on legal provisions. However, there are sociological factors which need to be addressed, such as social phenomena related to sharia banking dispute resolution. Methods of data collection were conducted through interviews, questionnaires, and literature studies. Data collected includes primary data and secondary data then will be analyzed qualitatively and identified and carried out categorization. From the results of the analysis, conclusions will then be drawn as answers to existing problems. With the issuance of Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning Religious Courts since 30 March 2006 has provided a legal umbrella for the implementation of Sharia Economics in Indonesia and disputes in sharia banking are the authority of the religious court environment, dispute resolution related to sharia banking economic activities completed in two ways, namely litigation and non-litigation, besides that the issuance of Law Number 21 of 2008 concerning Islamic Banking further reinforces the dispute resolution mechanism between the bank and the customer as stipulated in Article 55 paragraph (1), (2) and ( 3) that dispute resolution is carried out in accordance with the contents of the contract.